Corona, false alarm? : facts and figures - Reiß, Karina; Bhakdi, Sucharit (Chelsea Green Publishing, 2020)
The publication focuses on the progression of the coronavirus pandemic. Intended for the general public.
Keywords: pandemie; COVID-19; poskytování zdravotní péče; History, 21st Century; Betacoronavirus; Health Policy; Delivery of Health Care; History of Medicine; karanténa; pneumologie a ftizeologie; dějiny 21. století; veřejné zdravotnictví; infekční lékařství; Statistics as Topic; Quarantine; koronavirové infekce; Coronavirus Infections; statistika jako téma; dějiny lékařství; Pandemics; zdravotní politika